Analisis Yuridis Terhadap Pernikahan Beda Agama di Indonesia - Samantha Maria Yohen; Laurensia Clarissa Siva; Moody Rizqy Syailendra (VERITAS, 2023)
Marriage is a dimension of life that has religious value and is very important. Marriage is basically considered a sacred and holy thing, so that in each of these religions it relates the rules of marriage to their respective religions. The rules regarding marriage are contained in Law Number 1 of 1974. Based on Article 1 of Law Number 1 of 1974, marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household). based on the belief in the One and Only God. To support this writing, the authors use normative research, the type of data is primary and secondary legal materials. Using qualitative data analysis techniques. There are six religions in Indonesia, each of which has its own views on interfaith marriage, and it can be concluded that each of these six religions basically does not allow interfaith marriages